PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Heder, Heder; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of financial performance to the firm value and the influence of the implementation of good corporate governance to the correlation of financial performance to the firm value. The samples are manufacturing companies which are engaged in consumer goods industry sector which are listed in Indonesia Stock Exchange in 2012-2015 periods. The sample collection technique has been done by using purposive sampling, and 13 companies have been obtained as samples. This research has been done by using moderation regressions analysis and the SPSS (Statistical Product and Service Solutions). The result of the research shows that: (1) financial performance has significant and positive influence to the firm value. (2) Managerial ownership is the moderating variable to the correlation of financial performance to the firm value, meanwhile the institutional ownership is not a moderating variable.Keywords: financial performance, firm value, good corporate governance.